CDC7 Expression in Selected Odontogenic Tumors. (21st November 2022) - Jaafari-Ashkavandi, Zohreh; Alizadeh, Nahid
Abstract : Objectives . CDC7 is a serine-threonine kinase that plays a key role in initiating DNA replication. It has been implicated in the growth and invasion of many pathologic lesions and suggested as a diagnostic marker. The aim of this study was to evaluate CDC7 in some odontogenic tumors. Materials and Methods . In this cross-sectional study, 45 cases, including 19 ameloblastomas, 15 dentigerous cysts, 7 ameloblastic fibromas, and 4 adenomatoid odontogenic tumors (AOT), were studied immunohistochemically. ANOVA and post hoc methods were used for statistical analysis. Results . CDC7 expression was observed in 93% of tumors and all dentigerous cysts. The expression rate was low. The results showed a higher expression rate of CDC7 in ameloblastoma and ameloblastic fibroma compared to AOT (p = 0.009 and p = 0.048, respectively). Ameloblastoma and ameloblastic fibroma were not significantly different in CDC7 expression (p = 0.6 ). Conclusion . According to the results, the expression of the CDC7 protein in odontogenic tumors is low. The higher expression of CDC7 in ameloblastoma and ameloblastic fibroma in comparison with AOT confirms the hamartomatous growth of the latter, so it can be considered as a potential diagnostic marker. Future studies with a larger sample size are suggested to obtain a cut-off point for diagnostic purposes.